Project Based Learning Model to Improve Student Learning Outcomes in Islamic Education Learning at SD Negeri Alue Ie Itam - Afriana, Lena; Darni (ETNOPEDAGOGI: Jurnal Pendidikan dan Kebudayaan, 2025)
This study aims to improve the learning outcomes of sixth-grade students at Alue Ie Itam Public Elementary School on the topic of "Belief in the Day of Judgment" through the application of the Project-Based Learning (PjBL) model. The study used the Classroom Action Research (CAR) method, implemented in two cycles, each consisting of planning, action, observation, and reflection. The results showed that the implementation of PjBL increased the average student grade from 74.94 in Cycle I to 85.21 in Cycle II, with classical learning completion reaching 100% in Cycle II. The PjBL model was effective in improving students' understanding of the material and collaborative skills.